The Correlation Between Teachers' Feedback And Students' Writing Achievement In Academic Writing Class - Patty, Jusak; Binnendyk , Sophia; Kelirey , Abu Kasim (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2025)
This study investigated the correlation between teacher feedback and students' writing achievement in academic writing classes at Pattimura University, Indonesia. Using a quantitative correlational design, data were collected from 30 students through a 22-item Likert-scale questionnaire measuring perceptions of feedback and document analysis of final writing grades. Statistical analysis revealed a weak and statistically insignificant relationship between teacher feedback and students' writing achievement (r = 0.075; p = 0.695), indicating that positive perceptions of feedback do not automatically translate to improved writing performance. Students demonstrated positive perceptions of feedback (M = 4.18, High category) but showed lower scores in motivation and self-regulation (M = 3.93). Writing achievement exhibited clustering at developmental thresholds—particularly at minimum passing (55 points) and minimum excellence (85 points) levels. The findings suggest that feedback effectiveness is mediated by factors such as self-regulation abilities, motivation, and existing writing proficiency. This study contributes to feedback theory by demonstrating that feedback functions within a complex system of writing development rather than as an isolated intervention, highlighting the need for a paradigm shift toward creating learning environments where students develop skills to engage with feedback effectively.